2020
DOI: 10.3390/molecules25092076
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological (or Synthetic) and Nutritional Agonists of PPAR-γ as Candidates for Cytokine Storm Modulation in COVID-19 Disease

Abstract: The cytokine storm is an abnormal production of inflammatory cytokines, due to the over-activation of the innate immune response. This mechanism has been recognized as a critical mediator of influenza-induced lung disease, and it could be pivotal for COVID-19 infections. Thus, an immunomodulatory approach targeting the over-production of cytokines could be proposed for viral aggressive pulmonary disease treatment. In this regard, the peroxisome proliferator-activated receptor (PPAR)-γ, a member of the PPAR tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 62 publications
1
107
0
9
Order By: Relevance
“…In this context, natural PPAR-γ agonists present in foodstuffs could also act as anti-inflammatory molecules by inhibiting the expression of pro-inflammatory cytokines. Ciavarella et al (2020) have published a review where the anti-inflammatory effect of several natural compounds are summarized [62]: (a) EPA and DHA, provided by sea food and fish oil [63], (b) carvacrol, a monoterpenic phenol present in thyme and oregano, two plants of the Mediterranean area [64], (c) capsaicin, contained in hot pepper, one of the most used spices around the world [65], (d) carnosic acid and carnosol, two dipertenoids present in rosemary and sage [66,67], (e) punicic acid, contained in pomegranate seed oil [68], (f) citral, present in lemongrass oil [69], and (g) curcumin [70,71].…”
Section: Natural Ppar-γ Agonistsmentioning
confidence: 99%
“…In this context, natural PPAR-γ agonists present in foodstuffs could also act as anti-inflammatory molecules by inhibiting the expression of pro-inflammatory cytokines. Ciavarella et al (2020) have published a review where the anti-inflammatory effect of several natural compounds are summarized [62]: (a) EPA and DHA, provided by sea food and fish oil [63], (b) carvacrol, a monoterpenic phenol present in thyme and oregano, two plants of the Mediterranean area [64], (c) capsaicin, contained in hot pepper, one of the most used spices around the world [65], (d) carnosic acid and carnosol, two dipertenoids present in rosemary and sage [66,67], (e) punicic acid, contained in pomegranate seed oil [68], (f) citral, present in lemongrass oil [69], and (g) curcumin [70,71].…”
Section: Natural Ppar-γ Agonistsmentioning
confidence: 99%
“…Once PPAR-α and -γ agonism exerts multiple metabolic, inflammatory and immunologic benefits, pioglitazone has been proposed as a candidate against COVID-19 [282,332], despite the lack of current clinical trials to date. Pioglitazone may exert beneficial effects in the RAAS, including marked raise of serum ACE2 levels, which couples with SARS-CoV-2 and preclude viral coupling with attached ACE2 and consequent cell entry, and substantial increase of angiotensin- [1][2][3][4][5][6] and angiotensin-2 receptor (AT2) concentrations [333][334][335][336], undermining angiotensin II actions, may abolish acute lung injury by acting in a range of actions, including positively modulation of macrophage activity, reduction of neutrophil recruitment in response to endotoxin, and reduction of inflammation during sepsis [337][338][339][340][341], and also has direct anti-viral effects [342][343][344][345]. Due to its multiple pleiotropic effects, glitazones could theoretically be candidates for all stages in COVID-19 [332], and is currently being tested in one clinical trial [346].…”
Section: Of Minor Relevancementioning
confidence: 99%
“…This deficiency is accompanied by thinner collagen and connective tissue, reducing the number of antibodies in the physical barrier, which results in a favorable environment for the aggressor (165). Moreover, the protein-energy malnutrition associated with chronic diseases has been recognized as a virulence factor for severe COVID-19 because it can deregulate immune cell activation leading to increasing inflammation in the lungs and longer viral persistence (133,166). Moreover, it has been shown that COVID-19 patients require a diet rich in high energy nutrients (105-160 kj/kg/day or 25-40 kcal/kg/day) and proteins (167)(168)(169)(170).…”
Section: Effect Of Dietary Proteins and Amino Acids On The Immune Systemmentioning
confidence: 99%